Understanding the utilization of preventive health services for non-communicable diseases: a qualitative study with community members and family physicians - Şükran Peker; Ahmet Topuzoğlu; Seyhan Hıdıroğlu; Özlem Tanrıöver (BMC Primary Care)
Abstract Background Non-communicable diseases (NCDs) remain a significant global public health concern. This study aims to comprehensively explore the perspectives of both potential users of preventive health services and family physicians, with the goal of identifying key factors that influence the utilization of these services. Methods This qualitative study involved in-depth, face-to-face interviews with 29 participants selected through criterion sampling. Criterion sampling is a purposive sampling method in which participants are selected based on predefined criteria relevant to the research question. Data was analyzed thematically. After familiarization with the transcribed data, initial codes were generated independently by two researchers. These codes were reviewed collaboratively and grouped into broader themes that reflected patterns across the data set. Ethical approval and institutional permissions were obtained for the study. Results Of the 29 participants, five were family physicians (FPs), and 24 were community members aged 28–63, residing in a district of Istanbul. Barriers to accessing preventive health services among community members included insufficient information, misconceptions, and the dynamics of patient-physician relationships. Most community members had limited awareness of preventive services within the healthcare system, often associating ‘routine health check-up examinations’ with paid services in private healthcare institutions. Some participants with a family history of cancer or heart disease reported seeking follow-up care in private hospitals and expressed that healthcare staff were reluctant to perform check-ups without an existing disease. FPs varied in their approach; while some integrated preventive care into routine visits, others were demotivated by systemic challenges such as workload, weak referrals, and lack of feedback. Feelings of inadequacy and frustration were also noted among FPs. Preventive services were often limited to patients who proactively sought care, and FPs expressed concern about unnecessary patient visits stemming from low health literacy. Conclusions This study highlights context-specific factors that influence the use of preventive health services, as reported by both community members and family physicians in a district of Istanbul. Based on participants lived experiences, the findings suggest that increasing public awareness of available preventive services, improving communication between patients and providers, and strengthening institutional support mechanisms could facilitate greater engagement with preventive care.